Osteoporotic effect on bone repair in lumbar vertebral body defects in a rat model. (16th April 2018) - Sakata, Munehiro; Tonomura, Hitoshi; Itsuji, Tomonori; Ishibashi, Hidenobu; Takatori, Ryota; Mikami, Yasuo; Nagae, Masateru; Matsuda, Ken Ichi; Tanaka, Masaki; Kubo, Toshikazu
Introduction: The number of patients who suffered from osteoporotic vertebral fractures is increasing. Osteoporosis has been reported to affect the healing process using long bone models. However, few studies have reported using vertebrae. In this study, we created a bone defect in the anterior part of vertebral body in ovariectomized rat and evaluated the healing process. Methods: Fifty-six 12-week old Sprague Dawley rats were divided into ovariectomy (OVX) and sham operation groups. A bone defect was created in the vertebral body 8 weeks after the first surgery. In both groups, the vertebral bodies were harvested immediately or at 4, 8, or 12 weeks after the second surgery ( n = 7 at each time point). Bone volume (BV, mm 3 ), bone volume fraction (BV/TV, %), trabecular thickness (Tb.Th, mm), trabecular number (Tb.N, 1/mm), and trabecular separation (Tb.Sp, µm) were evaluated by micro-computed tomography to assess the new bone formation. Histological analysis was also performed. Results: The BV and the BV/TV were significantly lower at 4 and 12 weeks in the OVX group compared with those in the sham group. The Tb.Th was significantly lower at 8 and 12 weeks in the OVX group. Histologically, at 12 weeks, in the OVX group, the bone had a thinner, layered structure on the surface of the defect, and the trabecular structure was less dense. Conclusion: This study demonstrated that bone mass formation was suppressed and the quality of repaired bone was poor in the healing process of vertebral body defect under osteoporotic conditions. These findings could be the key to understand the pathology of osteoporotic vertebral fracture and to develop its therapies.